2001
DOI: 10.1046/j.1365-2281.2001.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac autonomic regulation after prolonged maximal exercise

Abstract: Harmful cardiac events occurs frequently after exercise. However, the cardiac autonomic regulation after vigorous exercise is not well known. This study was designed to assess heart rate (HR) variability before and after a 75 km cross-country skiing race. HR variability was assessed by using standard statistical measures along with spectral and quantitative Poincarè plot analysis of HR variability in 10 healthy male subjects (age 36 +/- 11 years). The average HR was at the same level 1 day after the race as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
176
5
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 28 publications
9
176
5
7
Order By: Relevance
“…Hynynen et al (2010) studied the effects of single moderate and heavy (marathon) endurance exercise sessions on nocturnal HRV, and found that both sessions affected nocturnal HR and HRV, HFP being only 77 % and 34 % of the nocturnal values of a resting day after moderate and heavy exercises, respectively. Hautala et al (2001) also reported decreased HRV during the night fol-lowing a 75 km cross-country ski-race, followed by a rebound phenomenon during the second night after the race. They also reported large interindividual variation in the recovery time of HFP to the pre-race level after the ski-race (0-14 h, mean 8.2 h).…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 85%
See 4 more Smart Citations
“…Hynynen et al (2010) studied the effects of single moderate and heavy (marathon) endurance exercise sessions on nocturnal HRV, and found that both sessions affected nocturnal HR and HRV, HFP being only 77 % and 34 % of the nocturnal values of a resting day after moderate and heavy exercises, respectively. Hautala et al (2001) also reported decreased HRV during the night fol-lowing a 75 km cross-country ski-race, followed by a rebound phenomenon during the second night after the race. They also reported large interindividual variation in the recovery time of HFP to the pre-race level after the ski-race (0-14 h, mean 8.2 h).…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 85%
“…It has been found in previous studies (Hautala et al 2001;Hynynen et al 2010;Mourot et al 2004) that the recovery of vagal modulation may be delayed even 24-48 h after a prolonged high-intensity exercise. In the present study, no differences were found in the nocturnal HR or HRV between the nights before and after the experimental exercises.…”
Section: The Effects Of Exercise Intensity On Post-exercise Hrvmentioning
confidence: 87%
See 3 more Smart Citations